KADAR ALBUMIN IBU HAMIL DITINJAU DARI PENGETAHUAN DAN TINDAKAN TENTANG GIZI DI WILAYAH KERJA PUSKESMAS MANDALA MEDAN - Siahaan, Ginta (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2018)
Pregnancy is a thing in life that can create a happy family, where there will be physical and mental changes that are naturally (Sigalingging, 2009). Nutritional problems that are often experienced by pregnant women is less Chronic Energy (KEK) and nutrition anemia. Cake during pregnancy will restrict fetal growth and risk BBLR. One of the parameters to determine the cake on the pregnant mother is to perform an examination of albumin. The low nutrient intake especially protein consumed during pregnancy as causes of nutrition disorders can be seen from the level of albumin blood pregnant. The trigger factor of lack of knowledge about nutrition and disregarding the pregnant mother to the condition of the pregnancy progresses, among others economic status level of education which is still very low and pregnancy at a young age. Maternal Nutrition knowledge is low, usually not followed by the action of good mothers to meet the nutrition intake during pregnancy progresses (Bahar, 2013). The general aim of this research is to know the relation of knowledge and action on nutrition with serum albumin pregnant in the working area of the Puskesmas Mandala Medan. This research is cohort studies with Cross Sectional design and data analyzed using the Chi Square Test to know the relation of knowledge and action on nutrition with serum albumin on the pregnant mother in the working area of the Puskesmas Mandala Medan. The results of the study showed that there are significant relationships between nutrition knowledge with serum albumin pregnant, and no significant relationships between the actions with serum albumin pregnant.